UAE: Cultural Representation and Re-Creating Emirates Environment in International Films and its Implications for Tourism - HSHAM ABURGHIF (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
This article aims to highlight the role and importance of the cinema in raising tourism, introducing the UAE's tourism potential, promoting and attracting tourism, and increasing local development. Because 'there is [.] a lack of data-driven academic research that measures the effects of film industry on local tourism' (Tkalec et al. 2017, p.705). Further, 'the impacts of film tourism still appear to be under-appreciated. Though the effects of film tourism can have significant long-term benefits' (Hudson, 2011, p. 165). Likewise, Connell and Meyer argue that 'understanding of the experiences of screen tourists in film and TV locations remains an emerging area of inquiry' (2009, p. 194). This article 'evaluates the effects of film industry on tourism outcomes' (Tkalec et al. 2017, p.705) in the UAE. The article interpreted the films' portrayal to reveal how UAE's culture and the environment were represented in the international movies filmed in the UAE. Cities of UAEs are not merely replicated in international films but constructed anew; reimagined, or repurposed according to filmmakers' and cinematographers' points of view and the role of those cities within that vision. Huge attention, however, is paid to representing the UAE's cities in international films. How do the filmmakers contribute to portraying the UAE and represent the knowledge on-screen in the filming process? Reviewing international filming in the UAE will explore possible answers to these informed questions.